GENDER AND AGE ASPECTS OF BIOENERGETICS PROCESSES IN EXPERIMENTAL PASSIVE TOBACCO SMOKING AND MONOSODIUM GLUTAMATE ADMINISTRATION - Rutska, A. V.; Krynytska, I. Ya. (International Journal of Medicine and Medical Research, 2019)
Background. Active smoking and exposure to passive smoke are responsible for more than 5 million deaths each year. At the same time, a characteristic feature of present food technologies is the use of food additives that are not always safe for human health, such as monosodium glutamate (MSG). Objective. The aim of the research was to determine the changes in mitochondrial enzymes activity in rats in case of passive tobacco smoke combined with prolonged administration of MSG in the sex and age aspects. Methods. The evaluation of bioenergetics processes in the mitochondria of circulating neutrophils was carried out using succinate dehydrogenase (SDG) and cytochrome oxidase (CO) activity. Results. Passive tobacco smoke combined with the MSG administration in mature male-rats is accompanied by a significant inhibition of bioenergetics processes, as evidenced by a decrease in succinate dehydrogenase activity by 47.1% (p<0.001) compared to the intact animals, which is by 27.9% (p<0.001) below this index in case of the isolated effect of tobacco smoke and reduction of cytochrome oxidase activity by 27.5% (p<0.001) compared to the control group. Conclusions. Thus, the findings suggest that low dose intake of monosodium glutamate enhances the ability of tobacco smoke to disrupt the cell's bioenergetics processes by affecting the respiratory chain function and generation of ATP. Therefore, it is advisable to investigate the established toxic doses of E621, as well as to study the molecular mechanisms of the ‘safe’ (allowed) doses of MSG effect on a living organism.